Constitutional Guarantees for the Independence of the Indonesian Pers: A Constitutional Law Perspective - Turnya Turnya; Susanto Susanto (Penerbit Goodwood, 2026)
Purpose: This study aims to analyze the constitutional guarantees for press independence in Indonesia from a constitutional law perspective, with particular urgency given the growing tension between press freedom and digital regulation in the post-reform era. Research Methodology: This study uses a normative legal approach with qualitative document analysis. Primary legal materials were obtained from the Constitutional Court website and Cabinet Secretariat archives. Secondary materials included scholarly books and journal articles. The analysis followed a five-step framework using grammatical, systematic, historical, and teleological interpretation methods. Results: Indonesia possesses a formally robust constitutional framework for press independence through Article 28F of the 1945 Constitution and Law Number 40 of 1999, which abolished the SIUPP licensing and prohibited censorship. The Constitutional Court upheld these protections in several rulings. However, significant implementation gaps persist, including the criminalization of journalists under the Electronic Information and Transactions (ITE) Law, government intervention, and inconsistent judicial enforcement. Conclusions: Constitutional guarantees for press independence in Indonesia are formally strong but are practically incomplete. Achieving full protection requires improved judicial enforcement and updated doctrinal interpretations that explicitly address digital journalism challenges, an area where current constitutional discourse remains underdeveloped. Limitations: This study relies on normative legal analysis without empirical data and covers court decisions only through 2014. Contributions: This study contributes to constitutional law by examining Indonesia’s press freedom framework and identifying implementation gaps, particularly regarding digital journalism regulation under the ITE Law. Its novelty lies in bridging constitutional press protection with emerging digital challenges.